Effects of Larval Diet on the Male Reproductive Traits in the West Indian Sweet Potato Weevils Euscepes postfasciatus (Coleoptera: Curculionidae) - Chihiro Himuro; Kinjo Misa; Atsushi Honma; Yusuke Ikegawa; Tsuyoshi Ohishi; Norikuni Kumano (Insects, 2022)
Larval diet significantly affects adult traits, although less is known about how they affect reproductive traits. Males of West Indian sweet potato weevil Euscepes postfasciatus deliver a remating inhibitor along with sperm to their mates during mating, leading to a refractory period (the period before females mate again). Crossing experiments were conducted using lines reared on artificial diets, including sweet potato powder (AD) or sweet potato tubers (SP) during the larval stage, and the refractory period was examined. We also examined whether the larval diet qualitatively or quantitatively altered male ejaculate. The results showed that the refractory period was significantly longer in the SP treatment than in the AD treatment for males and females. There was no significant difference in ejaculate volume. However, the number of sperm in the testes-seminal vesicles complex was significantly higher in the SP treatment. Additionally, SDS-PAGE revealed that the ejaculate was qualitatively different depending on the larval diet, and one protein of approximately 15 kDa in size was expressed only in the SP treatments. Revealing how larval diet affects reproductive traits in adult males will help shed light on the diverse evolution of insect mating systems and reproductive behavior.